For An Eritrean Culture, or a Culture of Resistance (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2014)
It is perhaps necessary to explain why this essay may seem in some way not directly related to the character of the contributions presented in April this year at the East-Africa Cities Lab Conference. Urbanization vs Human Survival (held at the Faculty of Architecture of Sapienza University of Rome) and now collected in this publication. This calling of mine â€“ which occurred after the conference itself â€“ thanks to a suggestion by Anna Irene Del Monaco, partly arose out of a shared feeling for â€œother culturesâ€, for the in-between lands, the peripheries in general, the Mediterranean, Oversea Countries. But especially it arose on account of my direct participation, between 1999 and 2000, in the phases of the design and subsequent construction of a State-owned hotel in Asmara, and on account of my later doctoral research completed in 2003, under the guidance of Lucio Barbera, my advisor. My dissertation, later published in 2006, already attempts in its title â€“ Architettura di retroguardia e laboratorio dâ€™oltremare. Per una scuola nazionale di architettura allâ€™Asmara [Rearguard Architecture and an Overseas Laboratory. For a National School of Architecture in Asmara] â€“ to offer some content which, after almost twelve years and despite being perhaps a bit schematic in parts, I think could still be of interest, at least in its presuppositions and in the thesis of the dissertation. I will summarize here in short paragraphs its main contents of this thesis, and some its hypotheses as to how to go forward. They address autonomous but interconnected themes, useful for reflection and thus suggesting possible ways â€“ between the past and the urgency of the contemporary â€“ ideally fostering an active â€œculture of resistanceâ€.